Refeeding syndrome in a woman with pancreatitis: a case report. Issue 2 (February 2021) - Lo Gullo, Alberto; Rifici, Carmela; Caliri, Santina; Donato, Antonina; De Cola, Maria Cristina; Di Cara, Marcella; Corallo, Francesco; Bramanti, Placido; Giuffrida, Clemente
Refeeding syndrome can occur in malnourished patients with acute pancreatitis who have electrolyte imbalances. Refeeding syndrome is characterized by severe electrolyte imbalances (mainly hypophosphatemia, hypomagnesemia, and hypokalemia), vitamin deficiency (mainly thiamine deficiency), fluid overload, and salt retention resulting in organ dysfunction and cardiac arrhythmias. We herein report a case involving a patient with severe pancreatitis and gallbladder stones who developed refeeding syndrome with shock and loss of consciousness. The patient was treated by opportune vitamin and electrolyte supplementation therapy and showed substantial improvement after 2 weeks of hospitalization, gaining the ability to eat small bites of solid food orally. Early diagnosis and treatment of refeeding syndrome may reduce morbidity and mortality in patients with acute pancreatitis. Patients should be fasted only if alimentation is contraindicated, and electrolyte values must be closely monitored.